Inverse scattering problems and their applications in various field of technology - Batrakov, D.O. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2023)
Relevance. The practical application of subsurface radar methods for solving the problems of diagnostics and assessing the state of technical objects, flaw detection of multilayer structurally inhomogeneous structures, searching for subsurface inhomogeneities of natural or artificial origin is based on estimating the parameters of the objects under study by the magnitude of the scattered characteristics. The solution of these problems is based on the solution of inverse scattering problems. Therefore, the development and improvement of methods for solving inverse problems of electromagnetic field scattering by subsurface inhomogeneities is an extremely urgent task of radiophysics. The purpose of work analysis of methods for solving inverse scattering problems for various scientific and technical applications. This is primarily the task of non-destructive testing and remote sensing of natural and artificial objects. Materials and methods. The analysis is based on the application of analytical methods, numerical simulation methods, statistical methods and experimental verification of the results obtained. The main attention is paid to the analysis of approaches based on the use of the Newton-Kantorovich scheme, the Tikhonov regularization method and the Pontryagin maximum principle for determining the electrical parameters of flat-layered media - the relative permittivity and, at the next stage, the geometric parameters of the structural layers. The results. Various approaches to solving inverse scattering problems, as well as their combinations, are analyzed. The main attention is paid to the results in the field of non-destructive testing and remote sensing using wave methods. The spheres of practical application of methods for solving inverse scattering problems are considered and possible directions for their development are formulated. Conclusions. The results of the analysis performed form the basis for the development of new methods for solving inverse scattering problems and for improving the previously proposed methods.